Improved varieties to make India self-sufficient in arecanut - Ananda, KS; Chowdappa, P (Indian Horticulture, 2019)
The present production of arecanut in the world is about 0.867 million tonnes from an area of 0.73 million ha. India ranks first in both area and production of arecanut. In India, arecanut is cultivated in 4.46 lakh ha with an annual production of 6.08 lakh tonnes. The area under arecanut in India has increased from 94,800 ha during 1956-57, to 4.46 lakh ha during 2012-13. The production for corresponding period has increased from 74,700 tonnes to 6.08 lakh tonnes. The productivity has also increased from 788 kg chali/ha to 1,363 kg/ha. The increase in pro-ductivity and production is due to development of high-yielding varieties coupled with supply of quality planting materials, better agrotechniques and plant-protection measures. Since India achieved self-sufficiency in arecanut production due to extensive research efforts of CPCRI, the strategy is to restrict area and enhance the productivity by replacing old and unproductive gardens with dwarf hybrids, empower small and marginal farmers through multiple cropping systems and intensify research efforts on alternate uses of arecanut to avoid market fluctuations.